Viana do Castelo. Dos planos existentes a um novo projeto urbano - Luis Rafael Pimenta Rodrigues (2020)
The present dissertation intends to understand the growth and expansion from the city of Viana do Castelo, for consequently develop a urban project, responding to the circumstances found in relation to the city and its considered plans. First, develops the most significant events that defined the urban mesh of the city, since the period of your foundation until the present day of the 21st century. This investigation develops mainly on the 20th and 21st centuries, especially in the Viana Polis program and in the Praia Norte requalification project, with the objective of understand the areas that were included and excluded in these projects, to consequently develop a urban reflection linking the various projects to the rest of the urban city mesh and taking the potential of the polis program to the nearest area with ocean front. In this first moment, it is still intended determine the main lines of force that are the base the current urban shape of the city of Viana do Castelo. The approach to the theme starts from the description of the intervention site, through an objective reading of the current circumstances of the place. In a second moment, intended to elaborate and understand the existences of the place, where a new urban project will be developed. Here, intended a deep analysis of this intervention territory, through of the search and study about your limits, appropriation, problems and potencial, among others. After of analysis is removed the important information to develop a urban strategy. Finally, the process developed to elaborate the design of a project is presented, as a way of implementing the adopted strategy. It intends to elaborate an urban plan with the objective of solving all the problems in this area, potentially being a response to the Viana Polis program.